Role of pilocarpine use following laser peripheral iridotomy in eyes with refractory acute angle closure glaucoma: A case report and literature review. Issue 27 (8th July 2022) - Yen, Chu-Yu; Chen, Chun-Chen; Tseng, Po-Chen
Abstract : Rationale: Angle closure glaucoma (ACG) is one of the most emergent types of glaucoma in clinical practice. Laser peripheral iridotomy (LPI) could minimize pupillary block and prevent ACG from an acute attack. However, recurrent increase in intraocular pressure (IOP) may still occur despite successful LPI. The aim of this study is to highlight the importance of postLPI pilocarpine use and larger LPI size as well as to share some experiences of cataract surgery in patients with ACG. Patient concerns: A 63-year-old female was referred to our hospital for headache, and poor control of IOP in the right eye for 3 hours. Diagnoses: The patient was diagnosed ACG in the right eye. Recurrence of ACG in the right eye and new-onset and recurrent ACG in the left eye were noted during follow-up, despite successful LPI. The diagnosis was confirmed through slit lamp and gonioscope examination. Interventions: The LPI size was enlarged and pilocarpine use was maintained at 2% (1 drop 4 times a day) in both the eyes. Finally, cataract surgery was performed in both the eyes. Outcomes: No recurrence of ACG was noted during postLPI pilocarpine use in both the eyes. The postoperative IOP was stable for >6 months after cataract surgery without any surgical intervention or antiglaucoma medication use. No discomfort or major complication was observed. Conclusion: This report highlights the importance of postLPI pilocarpine use and larger LPI size in patients with refractory ACG.